Synchronizing series-parallel deterministic finite automata with loops and related problems - Bruchertseifer, Jens; Fernau, Henning (RAIRO. Informatique théorique et applications, 2021)
We study the problem DFA-SW of determining if a given deterministic finite automaton A possesses a synchronizing word of length at most k for automata whose (multi-)graphs are TTSPL, i.e. , series-parallel, plus allowing some self-loops. While DFA-SW remains NP-complete on TTSPL automata, we also find (further) restrictions with efficient (parameterized) algorithms. We also study the (parameterized) complexity of related problems, for instance, extension variants of the synchronizing word problem, or the problem of finding smallest alphabet-induced synchronizable sub-automata.